Comparative Estimation of Maneuverability of the Multi-Track Road Trains of Different Layout Schemes - Volodymyr Sakhno; Igor Murovanyi; Oleksandr Razboinikov; Olekcii Palamarchyk; Valerii Dembitskyi (Communications)
Today, in the constructions of multi-link road trains, two main layout schemes are used, as a rule - trailer (car + n trailers) and semi-trailer (tractor car + n semi-trailers). Previously conducted studies established that the maneuverability indicators of the road trains can be determined on wheels rigid in the lateral direction, that is, according to kinematic models, which are based on the angles of assembly of the road train links. These angles are defined for both a three-link trailer and a semi-trailer vehicle train, for different locations of the extended link. For the semi-trailer road trains, the requirements for maneuverability are not met, and therefore the trailer links must be equipped with more or less complex control systems. With a direct control drive on the front axles of the second and third semi-trailers, when turning at 90º and 180º, only the first layout scheme satisfies the requirements for maneuverability.